2022
DOI: 10.1155/2022/1108865
|View full text |Cite
|
Sign up to set email alerts
|

Theranostic Effect of Folic Acid Functionalized MIL‐100(Fe) for Delivery of Prodigiosin and Simultaneous Tracking‐Combating Breast Cancer

Abstract: The metal organic framework (MOF) member, MIL-100(Fe), is considered as attractive drug nanocarrier that may be due to the great porosity, colloidal stability, and biocompatibility. In the present study, the new electrochemical synthesis procedure was presented for MIL-100(Fe) building block, and secondly, folic acid (FA) was introduced to the structure for assessing its potential targeted ability to be entrapped by folic acid-positive breast cancer cells, MCF-7. Several techniques such as SEM, XRD, and FT-IR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The selective index from 3.21 to 12.48 indicated that folic acid nanoparticles could improve the anticancer potential of PG. [ 140 ]…”
Section: Prodigiosin and Drug Deliverymentioning
confidence: 99%
“…The selective index from 3.21 to 12.48 indicated that folic acid nanoparticles could improve the anticancer potential of PG. [ 140 ]…”
Section: Prodigiosin and Drug Deliverymentioning
confidence: 99%
“…The exceptional porosity and high surface area of these structures, together with tuning and designing of a variety of MOFs due to infinite combination of metal nodes and organic ligands, tailorable pore size, biocompatibility and biodegradability, and ease of functionalization of organic ligands, led to the vast potential and application of ions utilized in the synthesis include p-block elements, transition metals, alkaline earth metals, alkaline metals, lanthanides, and actinides [ 7 ]. Diverse applications of MOFs including gas storage, adsorption, separation, ion exchange, molecular recognition, sensing and detection, optics, catalysis, electrocatalysis, photovoltaics, imaging, and drug delivery are introduced [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ]. MOFs have been considered promising carriers in drug delivery systems, due to their high storage capacity and controlled release.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid nanoscale metal-organic frameworks (nanoMOFs) with large pore volumes and surface areas are a new class of versatile porous materials formed by the coordination of metal clusters and organic ligands ( Férey et al, 2005 ). More particularly, the biodegradable iron trimesate MIL-100(Fe) nanoMOFs (MIL stands for Materials of Institute Lavoisier) are considered among the most efficient materials as drug carriers ( Ettlinger et al, 2022 ) because of the following unique properties: 1) high drug loading capacity for drugs with different physicochemical properties ( Horcajada et al, 2009 ); 2) easily engineered multifunctional surfaces composed of targeting moieties ( Agostoni et al, 2015 ; Qiu et al, 2021 ; Mokhtarian et al, 2022 ); and 3) possibilities to conveniently attach fluorescent moieties for imaging purposes ( Li et al, 2020a ; Qiu et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%